2021
DOI: 10.1101/2021.12.03.21267036
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spike-specific T cells are enriched in breastmilk following SARS-CoV-2 mRNA vaccination

Abstract: We compared the phenotype, diversity, and antigen specificity of T cells in the breastmilk and peripheral blood of lactating individuals who received SARS-CoV-2 mRNA vaccination. Relative to blood, breastmilk contained higher frequencies of T effector and central memory populations that expressed mucosal-homing markers. T cell receptor (TCR) sequence overlap was limited between blood and breastmilk. Overabundant breastmilk clones were observed in all individuals, were structurally diverse, and contained CDR3 s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…These T cells were uniformly effector memory T cells and expressed increased levels of mucosal homing markers CCR9 and CD103 when compared to circulating T cells. Interestingly, the expression of CCR9 increased in relation to time since delivery and time since 2 nd vaccine dose further supporting that the mammary gland is a mucosal site where local T cells are stimulated and mature overtime (Armistead et al, 2021).…”
Section: B and T Cellsmentioning
confidence: 78%
See 1 more Smart Citation
“…These T cells were uniformly effector memory T cells and expressed increased levels of mucosal homing markers CCR9 and CD103 when compared to circulating T cells. Interestingly, the expression of CCR9 increased in relation to time since delivery and time since 2 nd vaccine dose further supporting that the mammary gland is a mucosal site where local T cells are stimulated and mature overtime (Armistead et al, 2021).…”
Section: B and T Cellsmentioning
confidence: 78%
“…CMV (Moylan et al, 2017), EBV (Sabbaj et al, 2005), HIV (Sabbaj et al, 2002) and influenza-specific (Ruben et al, 1982) T cells are detected in breast milk, are at higher frequencies than in peripheral blood, and expand during maternal or infant infection (Hassiotou et al, 2013a;Hassiotou et al, 2013b). In a recent report authors found spike-specific T cells after SARS-CoV-2 mRNA vaccination in lactating mothers (Armistead et al, 2021). These T cells were uniformly effector memory T cells and expressed increased levels of mucosal homing markers CCR9 and CD103 when compared to circulating T cells.…”
Section: B and T Cellsmentioning
confidence: 94%
“…Although studies about memory T cells against SARS-CoV-2 in human milk are scarce, Armistead et al observed that the lactating breast contains a distinct T-cell population that can be modulated by maternal vaccination with potential implications for infant passive protection. These researchers have identified SARS-CoV-2 spikespecific T cells in mRNA vaccinated in lactating women (89). Another study conducted by Goncalves et al involving lactating women who received mRNA vaccination found a combination of spike-reactive T cells and anti-SARS-CoV-2 secreted IgA in their milk, which shows that immune transfer to the infant could linger even after weaning, especially because of long-lived memory T cells transferred (64).…”
Section: Maternal Immune Cells In Human Milk and Cellular Immunity Tr...mentioning
confidence: 97%
“…Using animal models, it was shown that cells from milk can survive the digestive tract and can traffic into infant organs ( 112 , 113 ). Interestingly two recent studies have demonstrated the presence of SARS-CoV-2 specific Spike-reactive T cells in human milk after vaccination ( 111 , 114 ). However, it is unknown if human milk cells provide immune protection to the respiratory tract or gastrointestinal tract of human infants or if they are taken up in the infant gut into systemic circulation.…”
Section: Immune Responses In Human Milk Following Covid-19 Vaccinationmentioning
confidence: 99%